Kralj Ubu - šok snovalnega gledališča v nacionalni instituciji - Šorli, Maja (Amfiteater (Ljubljana), 2016)
The article deals with the production of Ubu the King, performed in the 2015/2016 season on the Main Stage of the Slovenian National Theatre (SNT) Drama Ljubljana, and discusses the production%s narrower (the production itself) and wider contexts (the place and time of the production) as well as the media reactions it triggered. The article outlines the concept of devised theatre and describes how it differs from the dramatic theatre prevalent in Slovenia. The authors believe that precisely because it adopted the principles of devised theatre and the "Cool Fun" genre on the stage of SNT Drama, the production of Ubu the King not only sparked numerous media responses but also marks an important achievement in the Slovenian performing arts production. The discussion also points out the fundamental deficiency of the production (conservative gender roles) and presents the storyline of this production as an attempt at historising devised theatre.
Keywords: avtorski projekti; Kralj Ubu; kratkočasno gledališče; seksizem; snovalno gledališče; sodobno gledališče; uprizoritve